Electrochemistry of Metal Chalcogenides - Bouroushian, Mirtat; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The author provides a unified account of the electrochemical material science of metal chalcogenide (MCh) compounds and alloys with regard to their synthesis, processing and applications. Starting with the chemical fundamentals of the chalcogens and their major compounds, the initial part of the book includes a systematic description of the MCh solids on the basis of the Periodic Table in terms of their structures and key properties. This is followed by a general discussion on the electrochemistry of chalcogen species, and the principles underlying the electrochemical formation of inorganic compounds/alloys. The core of the book offers an insight into available experimental results and inferences regarding the electrochemical preparation and microstructural control of conventional and novel MCh structures. It also aims to survey their photoelectrochemistry, both from a material-oriented point of view and as connected to specific processes such as photocatalysis and solar energy conversion. Finally, the book illustrates the relevance of MCh materials to various applications of electrochemical interest such as (electro)catalysis in fuel cells, energy storage with intercalation electrodes, and ion sensing.
Chalcogens and Metal Chalcogenides -- Electrochemistry of the Chalcogens -- Electrochemical Preparations I (Conventional Coatings and Structures) -- Electrochemical Preparations II (Non-conventional) -- Photoelectrochemistry and Applications -- Electrochemical Processes and Technology.
Keywords: Chemistry; Chemistry, inorganic; Materials; Chemistry; Electrochemistry; Materials Science, general; Inorganic Chemistry; Condensed Matter Physics